Antibacterial Activity Test of Citrus jambhiri L to inhibit the Growth of Aeromonas hydrophila - Ikhwanul Khairy; Henni Syawal; Morina Riauwaty (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Jungga acid (Citrus jambhiri L.) contains compounds such as limonene, flavonoids, and essential oils that have potential as natural antibacterial agents. This study was conducted from September 2024 to June 2025 at the Parasite and Fish Disease Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The objective of this study was to determine the antibacterial activity of jungga lime against Aeromonas hydrophila and to determine the MIC (Minimum Inhibitory Concentration). The methods used were experimental, employing the disk diffusion technique (Kirby-Bauer) to measure the clear zone and dilution methods (turbidity test and total plate count) to determine the MIC. The treatments consisted of jungga lime concentrations ranging from 100% to 1%, with a positive control using the antibiotic Oxytetracycline. Each treatment was repeated three times. The results showed that Jungga lime could inhibit the growth of A. hydrophila at concentrations ranging from 100% to 1%, with clear zone diameters of 13.93 mm to 6.56 mm. The best MIC value for inhibiting the growth of A. hydrophila was 0.6% (285 CFU/mL). It can be concluded that Jungga lime has potential as a natural antibacterial agent for controlling diseases in farmed fish